Kuwait : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Kuwait. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2017 Article IV Consultation highlights that non-oil growth in Kuwait has picked up modestly over the past two years, and inflation has moderated. After coming to a standstill in 2015, real non-hydrocarbon growth has recovered and is set to reach 2.5 percent in 2018, driven by improved confidence. Notwithstanding the impact of higher energy and water prices, inflation is on track to reach a multiyear low of 1.75 percent in 2017, owing to a decline in housing rents and favorable food price developments. The government's underlying fiscal position has improved on the back of spending restraint, but financing needs have remained large.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet